Once dead, twice shy - Harrison, Kim, 1966- (New York : HarperTeen, 2009)
Spunky teen Madison, though technically dead, uses a stolen amulet to retain the illusion of a body and help her in the struggle between Light and Dark reapers.
Keywords: Dead -- Fiction; Death -- Fiction; Occultism. -- Fiction